Colombia : 2011 Article IV Consultation: Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Colombia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Colombian economy proved resilient to the global financial crisis, and a solid recovery is under way. The pace of monetary tightening envisaged strikes the right balance between restraining credit growth and mitigating incentives for further capital inflows. A sudden acceleration of domestic demand places an additional burden on monetary policy. Colombia's financial sector oversight is solid, and plans to strengthen cross-border and consolidated supervision are commended. Steep taxation of labor and a relatively high minimum wage are significant hindrances to competitiveness. Colombia's exchange restrictions remain unchanged.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet